2018
DOI: 10.1093/ecco-jcc/jjy001
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Expression Analyses Identify a Disease-Modifying Variant for Fibrostenotic Crohn’s Disease

Abstract: We have identified a variant in WWOX and in lncRNA RP11-679B19.1 as a disease-modifying genetic variant associated with recurrent fibrostenotic CD and replicated this association in an independent cohort. WWOX can potentially play a crucial role in fibrostenosis in CD, being positioned at the crossroads of inflammation and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…In agreement with this observation, evidence from studies in various inflammatory pathologies strongly suggests that Wwox has a relevant function in inflammation in general. Furthermore, a direct association between WWOX and the NF-kB inflammation signaling pathway has been demonstrated [24][25][26][27]. observation, evidence from studies in various inflammatory pathologies strongly suggests that Wwox has a relevant function in inflammation in general.…”
Section: Wwox Expression In Cnsmentioning
confidence: 95%
“…In agreement with this observation, evidence from studies in various inflammatory pathologies strongly suggests that Wwox has a relevant function in inflammation in general. Furthermore, a direct association between WWOX and the NF-kB inflammation signaling pathway has been demonstrated [24][25][26][27]. observation, evidence from studies in various inflammatory pathologies strongly suggests that Wwox has a relevant function in inflammation in general.…”
Section: Wwox Expression In Cnsmentioning
confidence: 95%
“…Microbial DNA profiles and RNA-sequencing profiles from the intestinal biopsies of the RISK cohort have uncovered RNA-microbe interactions and shown that biopsies taken from the distal colon can predict the IBD disease location higher up in the intestine [7, 14]. In addition, stool samples from the PRISM cohort have also been used to discover microbial profiles that can predict the efficacy of vedolizumab, a biological drug regulating T-cell homing to the gut [15], while a genetic variant in the WWOX gene discovered using genotypes of IBD patients treated in our hospital can be used to assess the risk of stricturing and penetrating Crohn’s disease behavior [16].…”
Section: Introductionmentioning
confidence: 99%
“…is might be explained by differences in disease duration, the development of fibrosis prior to medication, or genotypic and phenotypic differences between patients. An allele that could lead to overexpression of the main profibrotic mediator, TGF-β, has been identified [8], which could lead to more rapid development of fibrosis and strictures. Another explanation could be that inflammation and fibrosis are initially linked in the pathogenesis, but later become two independent processes [9].…”
Section: Discussionmentioning
confidence: 99%